2010
DOI: 10.1016/j.joca.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of association between GDF5 polymorphisms and congenital dislocation of the hip in a Caucasian population

Abstract: This study reports, for the first time, the association between GDF5 polymorphisms and CDH in Caucasians, and points out another polymorphism of interest that requires further investigation. Reduction in GDF5 expression might lead to developmental deficiency of ligaments and capsule in hip joint, and therefore contribute to CDH pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 45 publications
(32 reference statements)
3
50
0
Order By: Relevance
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The reduced activity of GDF5 may inhibit the process of early cartilage differentiation (Hatakeyama et al, 2004). Genetic variations in the GDF5 locus have been reported to be involved in the pathogenesis of rheumatoid arthritis and to influence human height, hip axis length and fracture risk in the elderly (Rouault et al, 2010;Vaes et al, 2009). Furthermore, association of variant T allele with other musculoskeletal phenotypes, including variation in Achilles tendon pathology, fracture risk and congenital dysplasia of the hip, has also been reported (Posthumus et al, 2010;Sanna et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that female babies are at higher risk due to their susceptibility to the maternal hormone relaxin, which may contribute to ligamentous laxity in the hip joint (Maclennan and Maclennan, 1997). There is limited information on what genes may be responsible for the familial incidence of DDH, with most studies proposing an association between a genetic or chromosome variant and DDH being focussed on individual families or single ethnicities (Dai et al, 2008;Feldman et al, 2010;Feldman et al, 2012;Hao et al, 2014;Rouault et al, 2010;Tian et al, 2012), limiting their impact on the wider population. However, evidence that GDF-5 may be linked with DDH has been revealed for both Chinese Han (Dai et al, 2008) and western Brittany (Rouault et al, 2010) patient groups.…”
Section: Risk Factorsmentioning
confidence: 99%
“…There is limited information on what genes may be responsible for the familial incidence of DDH, with most studies proposing an association between a genetic or chromosome variant and DDH being focussed on individual families or single ethnicities (Dai et al, 2008;Feldman et al, 2010;Feldman et al, 2012;Hao et al, 2014;Rouault et al, 2010;Tian et al, 2012), limiting their impact on the wider population. However, evidence that GDF-5 may be linked with DDH has been revealed for both Chinese Han (Dai et al, 2008) and western Brittany (Rouault et al, 2010) patient groups. Intriguingly, abnormal GDF-5 expression has been shown in the elbow joints of immobile "muscleless limbs" mouse embryos (Kahn et al, 2009), which undergo aberrant shape morphogenesis (Kahn et al, 2009;Nowlan et al, 2010a).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Previously, other SNPs have been shown to be associated with DDH development [5,6], but this is the first time to suggest association between another two SNPs (rs224332 and rs224333) and DDH.…”
mentioning
confidence: 88%